Baseline risk factor prevalence among adolescents aged 15–17 years old: findings from National Non-communicable Disease Monitoring Survey (NNMS) of India. Issue 6 (29th June 2021) - Mathur, Prashant; Kulothungan, Vaitheeswaran; Leburu, Sravya; Krishnan, Anand; Chaturvedi, Himanshu Kumar; Salve, Harshal Ramesh; Amarchand, Ritvik; Nongkynrih, Baridalyne; Ganeshkumar, Parasuraman; Urs K S, Vinay; Laxmaiah, A; Boruah, Manjit; et al.
Abstract : Objective: To generate national estimates of key non-communicable disease (NCD) risk factors for adolescents (15–17 years) identified in the National NCD Monitoring Framework and, study the knowledge, attitudes and practices towards NCD risk behaviours among school-going adolescents. Design and setting: A community-based, national, cross- sectional survey conducted during 2017–2018. The survey was coordinated by the Indian Council of Medical Research—National Centre for Disease Informatics and Research with 10 reputed implementing research institutes/organisations across India in urban and rural areas. Participants: A multistage sampling design was adopted covering ages between 15 and 69 years—adolescents (15–17 years) and adults (18–69 years). The sample included 12 000 households drawn from 600 primary sampling units. All available adolescents (15–17 years) from the selected households were included in the survey. Main outcome measures: Key NCD risk factors for adolescents (15–17 years)—current tobacco and alcohol use, dietary behaviours, insufficient physical activity, overweight and obesity. Results: Overall, 1402 households and 1531 adolescents completed the survey. Prevalence of current daily use of tobacco was 3.1% (95% CI: 2.0% to 4.7%), 25.2% (95% CI: 22.2% to 28.5%) adolescents showed insufficient levels of physical activity, 6.2% (95% CI: 4.9% to 7.9%) were overweight and 1.8% (95% CI: 1.0% to 2.9%) were obese. Two-thirds reported being imparted health education on NCD risk factors in their schools/colleges. Conclusion: The survey provides baseline data on NCD-related key risk factors among 15–17 years in India. These national-level data fill information gaps for this age group and help assess India's progress towards NCD targets set for 2025 comprehensively. Though the prevalence of select risk factors is much lower than in many developed countries, this study offers national evidence for revisiting and framing appropriate policies, strategies for prevention and control of NCDs in younger age groups.